(untitled) (Costos y Gestión, 2021)
The article studies the cases of poly-production companies with common restrictors that are operating in optimal market conditions with wasted productive and / or commercial capacity, focusing on variable cost optimization projects that allow a proportion of the reduction obtained to be transferred to price, in search of the triple objective: maximization of market share, maximization of profits and use of idle capacity. It is part of the development of quadratic models for optimizing prices and product mixes in the face of restrictions in contexts of competitive markets, where income functions have a non-linear behavior due to the need to reduce price to increase the volume of sales, considering price-demand elasticity as a relevant variable of the model. The modeling is presented at a theoretical and practical level, supported by a spreadsheet with widely used non-linear operational research functions.